2019
DOI: 10.1177/1468017319860663
|View full text |Cite
|
Sign up to set email alerts
|

Mental health social work in multidisciplinary community teams: An analysis of a national service user survey

Abstract: Summary The article addresses the continued lack of clarity about the role of the mental health social worker within community mental health teams for working age adults and particularly the limited evidence regarding this from the perspective of service users. It compares findings from the literature, found to originate from a predominantly professional viewpoint, with secondary analysis of a national survey of service users to assess their views. Findings Three particular aspects of mental health social work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…This qualitative paper forms part of a larger-mixed methods study that aimed to identify the social work contribution to CMHTs drawing on the characteristics, opinions and experiences of managers, practitioners and service users (Boland et al., 2019; Wilberforce et al., 2019). The views of social workers and their team colleagues were collected via focus groups and analysed using Braun and Clarke’s organic thematic analysis method (2016).…”
Section: Methodsmentioning
confidence: 99%
“…This qualitative paper forms part of a larger-mixed methods study that aimed to identify the social work contribution to CMHTs drawing on the characteristics, opinions and experiences of managers, practitioners and service users (Boland et al., 2019; Wilberforce et al., 2019). The views of social workers and their team colleagues were collected via focus groups and analysed using Braun and Clarke’s organic thematic analysis method (2016).…”
Section: Methodsmentioning
confidence: 99%
“…In the first stage, the lay members of the research team met to discuss what they perceived as being the contribution of social work to their mental health support, with a researcher acting as scribe. This discussion was informed by the research team's prior literature review on social work in mental health (Boland et al, 2019). The group arrived at fortysix 'statements' describing what they valued from social workers, organised into three themes: (i) social worker values; (ii) skills, knowledge and experience; and (iii) activities and tasks.…”
Section: Methodsmentioning
confidence: 99%
“…Existing evidence, as limited as it is, provides some initial insights. Evidence reviews (Penhale and Young, 2015;Boland et al, 2019), drawing mostly on qualitative evidence, found many personal and values-based qualities crucial to social work across the profession, including honesty, integrity, warmth, openness, courtesy, positivity, reliability and compassion. Many have referenced qualities akin to friendship, or at least a reciprocal relationship with social workers offering a sense of equality between people of equal worth (Penhale and Young, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Abendstern et al explored multi-disciplinary perceptions of the role of social work in mental health services in England and highlighted social work’s role in promoting the service users’ voice and in implementing the social model [ 14 ]. In exploring service users’ views of social work in mental health services, Boland et al suggested that there may be less of a clear understanding of social work’s distinctive role [ 15 ].…”
Section: Literature Reviewmentioning
confidence: 99%